Comparing the network structure of ICD-11 PTSD and complex PTSD in three African countries. (April 2021) - Levin, Yafit; Hyland, Philip; Karatzias, Thanos; Shevlin, Mark; Bachem, Rahel; Maercker, Andreas; Ben-Ezra, Menachem
Abstract: Background: Symptom network analysis has become an essential tool for researchers and clinicians investigating the structure of mental disorders. Two methods have been used; one relies on partial correlations, and the second relies on zero order correlations with forced-directed algorithm. This combination was used to examine symptom connections for ICD-11 Posttraumatic Stress Disorder (PTSD) and Complex PTSD (CPTSD) as the symptoms for these disorders have been known to be organized in a multi-dimensional and hierarchical fashion. We aimed to examine whether networks of ICD-11 CPTSD symptoms reproduced across samples from three African countries. Methods: We produced network models based on data from 2524 participants in Nigeria (n = 1018), Kenya (n = 1006), and Ghana (n = 500). PTSD and CPTSD symptoms were measured using the International Trauma Questionnaire (Cloitre et al., 2018). Results: The CPTSD network analysis using force-directed method alongside partial correlations based on Gaussian Graphical Models (GGM) revealed the multidimensional-hierarchal structure of CPTSD. The within-cluster symptoms of Disturbances in Self Organization (DSO) and PTSD were strongly correlated with each other in all networks, and the cross-cluster symptoms were lower. The most central symptom was 'feelings of worthlessness', a symptom of Negative Self-Concept that is part of the CPTSD cluster. The networks were very similar across the three countries. Conclusions: Findings support the ICD-11 model of PTSD and CPTSD in three African countries.